Identification of the Grapefruit (Citrus paradisi) Isocitrate Dehydrogenase Gene and Functional Analysis of CpNADP-IDH1 in Citric Acid Metabolism - Longfei Jin; Yang Yue; Feng Liu; Mingxia Wen; Bei Huang; Peng Wang (Horticulturae)
Citric acid serves as the principal organic acid in citrus fruits, with its concentration critically determining fruit flavor and market acceptability. Isocitrate dehydrogenase (IDH), a key enzyme in citric acid metabolism, mediates the conversion of citrate to α-ketoglutarate. This study cloned six candidate genes encoding IDH from grapefruit (Citrus paradisi). Bioinformatics analysis showed that all six genes contained the typical characteristic structure of IDH. Gene expression analysis found that CpNADP-IDH1 is highly expressed in mature and low-acid varieties. Overexpression of CpNADP-IDH1 significantly increased IDH enzyme activity and decreased citric acid content in transgenic grapefruit callus. These results showed that at least six genes encoding IDH exist in grapefruit, among which CpNADP-IDH1 catalyzes the decomposition of citric acid and regulates the organic acid content in fruits at maturity. CpNADP-IDH1 can be used as a candidate gene for molecular breeding of low-acid citrus varieties and as an essential target gene for developing citrus cultivation technology for reducing acid content.